Antimicrobial activity of ellagic acid against Helicobacter pylori isolates from India and during infections in mice. (16th March 2018) - De, Ronita; Sarkar, Avijit; Ghosh, Prachetash; Ganguly, Mou; Karmakar, Bipul Chandra; Saha, Dhira Rani; Halder, Aniket; Chowdhury, Abhijit; Mukhopadhyay, Asish K
Abstract: Objectives: Because of the rise in antimicrobial resistance, an inexpensive, diet-based treatment against Helicobacter pylori infection would be of great interest. The present study was performed to assess the in vitro effects of ellagic acid against clinical H. pylori strains that were resistant to antibiotics used for therapy and also to observe the morphological structure following treatment with ellagic acid. The effectiveness of ellagic acid in eradicating H. pylori infection in a murine (C57BL/6) infection model, one of the standard inbred mouse lines often used for experimental infection, was also assessed. Methods: A total of 55 strains were screened. The agar dilution method was used to determine the susceptibility of isolates to test compounds. Transmission electron microscopy was used to observe the morphology following treatment with ellagic acid. The antibacterial activity of ellagic acid in an H. pylori SS1-infected mouse model and its effect on gastric mucosal injury were determined by histology and PCR. Results: Ellagic acid inhibited the growth of all 55 of the H. pylori strains tested. The MIC of ellagic acid ranged from 5 to 30 mg/L, showing its bactericidal properties in vitro . Ellagic acid also demonstrated anti- H. pylori efficacy in eradication of this organism in an in vivo model, as well as restitution and repair of H. pylori -induced gastric mucosal damage. Conclusions: The present study paves the way for the preventive and therapeutic use of ellagic acid against H. pylori infection and, thus, ellagic acid can be considered a promising antibacterial agent against H. pylori -associated gastroduodenal diseases in humans.